Development of microtextures on polymer surfaces using the transfer method from metal templates - Myronyuk, Oleksiy; Baklan, Denys; Bilousova, Anna; Strashenko, Volodymyr (Technologies and Engineering, 2026)
Scaling up technologies for creating relief surfaces with controlled wetting properties is a pressing issue for the development of functional polymer materials. There is a need to investigate the patterns of transfer of micro- and nanotextures from metal templates to polymer substrates. The purpose of the study was to determine the influence of the replication method and polymer properties on the accuracy of relief reproduction and the development of water-repellent surface characteristics. Three replication methods were used for this purpose: obtaining polycarbonate film from a solution, reaction moulding using polydimethylsiloxane elastomer, and thermoforming of polyethylene films. The negative copies obtained were used as intermediate forms (polycarbonate) for creating positive replicas from polyethylene and polysiloxane. The hydrophobicity of the materials was evaluated by measuring the contact angles in directions parallel and perpendicular to the texture orientation. The results showed that all methods ensure the reproduction of periodic structures. However, the level of accuracy depends on the viscosity of the medium and the temperature conditions, with the lowest level of accuracy observed for polycarbonate and the highest level observed for polyethylene. Polycarbonate negatives were characterised by high detail of microdefects (up to 5 µm), while polyethylene films showed smoothing of the relief. Silicone positives most fully preserved the geometry of the original textures with defects. The study of surface hydrophobicity showed a significant increase in contact angles on structured surfaces compared to smooth ones, especially with parallel orientation. The maximum contact angles reached 140°C for polysiloxane and 139°C for polyethylene replicas of the structure with regular grooves. The practical significance of the study lay in identifying the optimal materials and methods for creating polymer surfaces with increased water repellency. Polycarbonate is suitable for use as an intermediate material for accurate texture copying, while silicone and polyethylene have potential for use as functional surfaces in protective coatings and liquid-infused porous surfaces.